System identification by discrete rational atoms. (June 2015) - Chen, Qiuhui; Mai, Weixiong; Zhang, Liming; Mi, Wen
Abstract: A novel adaptive frequency-domain system identification method for linear time-invariant systems is proposed in this paper. It finds poles for discrete rational atoms with discrete frequency responses. The theoretical foundation, including adaptive decomposition principle and decomposition convergence rate, is established. The algorithm of the adaptive pursuit is also provided in this paper.